Sustainability of the state system in the context of digital transformation - V. A. Kornilovich; K. A. Aramyan; A. V. Milekhin; A. V. Mironov (Цифровая социология)
The digital transformation of the structural components of the state system forms new socio-organizational forms and practices of political interaction. The transformation process is based on the dialectical overcoming of existing elements of the old order, the development of new goals and the formation of new specific ways to achieve them. As a result of the digital transformation of the structural components of the state system, new socio-organizational forms and practices of political interaction are being formed. Before our eyes, the transition of initially networked social formations into political offline processes is unfolding, new power resources and mechanisms of influence on the political organization as a whole are emerging in society. These processes relate to social self-organization and are characteristic of the adaptive algorithm of social changes. At the same time, changes in system parameters do not violate the contours of the existing state system. However, in the conditions of deliberate stimulation by the authorities of the digital transformation of all spheres of society’s life, the limited ability of the political system and the state to ensure the manageability of social and political processes is more clearly manifested.The article considers the process of deformation of the state system caused by the digitalization of public relations, analyses changes in theoretical models of explaining social reality and related changes in the organization of the political system and political practices.The multi-component nature of the impact of the global ICT paradigm on the sphere of public administration of a particular state is noted. In the era of the diversity of broadcast information, the dominance of the mass media and social networks, the public becomes a mass / crowd and an object of manipulation. The impact of information and communication technologies on the functioning of society is manifested in maintaining the gap between formal and informal institutions, intensive introduction of innovations, launching new mechanisms of social inequality, and the like, as a result, the integrity of the social system is violated. The risk of loss of manageability of social processes increases due to the fact that the recommendations for authorities on digital transformation, as well as most scientific publications on the topic of digitalization of public administration do not contain a critical assessment of the ICT paradigm itself and the concepts, concepts and practices formed on its basis.